Penguatan Pendidikan Moral terhadap Remaja di Era Globalisasi - Mariyana, Weni; Asy'arie, Bima Fandi; Fathorrozy, Fathorrozy (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2024)
Considering that moral education is currently always a topic of discussion in every educational activity both in schools and madrasas, a comprehensive strategy is urgently needed that can help teenagers improve their morals to understand cultural diversity and contribute positively. This research aims to identify and describe strengthening moral education for teenagers in the current era of globalization. The method used is library research using a qualitative approach. The results of this research show that improving moral education in adolescents includes: Providing good attitudes, Providing understanding through real examples, Providing moral education programs, Providing family involvement in building cooperation with the school, Providing assertiveness in socializing, Providing space for open communication. Provide multicultural education, Provide space for self-evaluation. Through all these methods, you can certainly develop the morals of teenagers so that they are not affected by increasingly rapid technological developments.